2020
DOI: 10.1039/d0tc03965a
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular H-bond design for efficient orange–red thermally activated delayed fluorescence based on a rigid dibenzo[f,h]pyrido[2,3-b]quinoxaline acceptor

Abstract: High-efficiency orange and red thermally activated delayed fluorescent (TADF) organic light-emitting diodes were fabricated based on a pair of isomers 3,6,11-triAC-BPQ and 3,6,12-triAC-BPQ, containing rigid dibenzo[f,h]pyrido[2,3-b]quinoxaline (BPQ) core and three...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Because trisubstituted acridine-based emitter showed good device performance, in 2020, Tang et al increased the acceptor strength and rigidity by attaching pyridine unit with dibenzophenazine core. [20] The donor substituted at the alpha position to pyridine unit based 3,6,11-triAC-BPQ showed high PLQY of 75 % compared to that of beta substituted 3,6,12-triAC-BPQ (53 %). Attaching donor at beta position lowered the singlet and triplet energies, so 3,6,12-triAC-BPQ was able to achieve much lower ~EST (0.03 eV) and red-shifted PL emission of 607 nm.…”
Section: High Rigid Heteroaromatic Based Orange Red Tadf Emittersmentioning
confidence: 93%
“…Because trisubstituted acridine-based emitter showed good device performance, in 2020, Tang et al increased the acceptor strength and rigidity by attaching pyridine unit with dibenzophenazine core. [20] The donor substituted at the alpha position to pyridine unit based 3,6,11-triAC-BPQ showed high PLQY of 75 % compared to that of beta substituted 3,6,12-triAC-BPQ (53 %). Attaching donor at beta position lowered the singlet and triplet energies, so 3,6,12-triAC-BPQ was able to achieve much lower ~EST (0.03 eV) and red-shifted PL emission of 607 nm.…”
Section: High Rigid Heteroaromatic Based Orange Red Tadf Emittersmentioning
confidence: 93%
“…Incorporation of heteroatoms to induce attractive intramolecular interactions, most commonly N•••H hydrogen bonds, is also now frequently reported (see Supporting Information section 2 for selected relevant examples). [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]63 In this latter approach, improved quantum yields, narrower emission spectra, or enhanced SOC compared to control materials are commonly attributed to N intramolecular interactions in the heteroatom-substituted material. 43−57 Although plausibly arising from increased D-A planarization (shifting toward a more optimum "compromise" average geometry) or rigidification of the molecular structure (deactivating some vibrational quenching pathways) direct evidence for intramolecular H-bonding is, to the best of our knowledge, only ever inferred rather than conclusively demonstrated.…”
mentioning
confidence: 99%
“…Reports in which the D-A geometry is influenced by external groups to understand or control TADF properties are now commonplace. , Successful strategies can include rigidification of the overall D-A structure or major modification of the average molecular geometry (including D-A angle or axial/equatorial conformers) through molecular design. Incorporation of heteroatoms to induce attractive intramolecular interactions, most commonly N···H hydrogen bonds, is also now frequently reported (see Supporting Information section 2 for selected relevant examples). , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Adversely, it was reported that a hydrogen bond was used to enhance the luminescence efficiency by forming emissive excimers, manipulating the molecular assembly, inducing the antiparallel supramolecular dimer, forming short hydrogen bonding networks between nonaromatic proteins, or suppressing nonradiative processes and triplet formation in recent years. 25,26 Typically, water molecules act as a classic fluorescence quencher for organic fluorophores to compete with the radiative process, which also commonly could be utilized as the poor solvent to build AIE aggregates. However, the effect of the intermolecular hydrogen bond especially between the solvent and AIE aggregates on their fluorescence properties is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%